El reto del Contador Público Frente a las Normas Internacionales de Información Financiera (Revista "Boletín el Conuco", 2020)
Today the public accountant is the best person to address the issue of convergence of International Financial Reporting Standards (IFRS), which is why he places the responsibility for implementing these standards within organizations. The CPA has the challenge of facing an objective and competent standardization of accounting rules so because Colombia decides to enter the international market, which requires a number of improvements in financial reporting, which should be clear descriptive, allowing analysis and is useful when making decisions.This process is an opportunity for CPAs erase the paradigm that has characterized so much time, which is based on its sole function is to recordtransactions in the accounting systems, which is reflected in simple numbers. Then it’s up to them to make appropriate changes and reform thisthought, demonstrating with actions that have the capabilities to provide solutions within an organization.
Keywords: convergence; transition; implementation; IFRS